Efeito da terapia fotodinâmica antimicrobiana com urucum e led na redução da halitose– ensaio clínico controlado e randomizado - Gonçalves, Marcela Leticia Leal (2018)
Halitosis, also known as bad breath, is a term used to define an unpleasant and foul odor that emanates from the mouth and may have local or systemic origin. This project aimed to verify if the treatment with antimicrobial photodynamic therapy (aPDT) with annatto and a light emitting diode (LED) is effective against it. A total of 44 students or UNINOVE employees with a diagnosis of halitosis were selected, presenting sulfite (SH2) ≥ 112 ppb in gas chromatography. The patients were randomly divided into 3 groups, which received different treatments: Group 1 (n=15): aPDT applied in the region of the back and middle thirds of the tongue; Group 2 (n=14): treatment with tongue scraper; Group 3 (n=15): combined treatment of tongue scraper and aPDT. For aPDT, annatto was used in a concentration of 20% (Fórmula e Ação®) applied in sufficient amount to cover the back and middle third of the tongue for 2 minutes for incubation, associated with a LED (Valo Cordless Ultradent®). Six points were irradiated on the back of the tongue with a distance of 1 cm between the points, considering the halo of light scattering and effectiveness of aPDT. The apparatus was previously calibrated at wavelength 395-480 nm for 20 seconds and energy of 9.6 J per point. The results of the halimetry were compared before, immediately after treatment and 7 days after. For the analysis of data from the Oral ChromaTM, the Friedman test was used for the intragroup analysis and the Kruskal Wallis test for the intergroup analysis. In all groups, there was a statistically significant difference between the initial sulfhydride value and the value immediately after the treatment (p <0.05). In Groups 1 and 3, there no was difference between the baseline value and the control of seven days. In Group 2, these times were not similar. There was no statistical difference between treatments.